2019
DOI: 10.1620/tjem.249.237
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relation between Glottal Closure and Plasma Substance P: A Study Protocol

Abstract: Glottal incompetence, i.e., reduced ability to produce effective glottal closure, is a problem often associated with aging. The study protocol is presented to determine whether blood substance P (SP) serves as an indicator of glottal closure function among the elderly. SP is involved in the neuromuscular mechanisms of cough; reduced concentration of SP may be a marker for increased risk of aspiration pneumonia. The antihypertensive angiotensin-converting enzyme inhibitor, which also inhibits degradation of SP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…MPT is used as an indirect assessment of laryngeal and vocal cord movements, and its relationship with aspiration is known [ 31 ]. In addition, it was reported that MPT can be an indicator of the glottic closure required for intrathoracic compression in the process of coughing [ 32 , 33 ]. It is straightforward to understand that MPT depends on the vital capacity, age, and sex.…”
Section: Discussionmentioning
confidence: 99%
“…MPT is used as an indirect assessment of laryngeal and vocal cord movements, and its relationship with aspiration is known [ 31 ]. In addition, it was reported that MPT can be an indicator of the glottic closure required for intrathoracic compression in the process of coughing [ 32 , 33 ]. It is straightforward to understand that MPT depends on the vital capacity, age, and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data in the protocol paper [ 14 ] associated with this study, the recommended sample size of participants was calculated using G*Power (version 3.1) [ 18 ] with power = 0.95, α = 0.05 and d = 0.5, producing an estimate of n = 105. The study included 122 patients (outpatients), all over the age of 65, each of whom provided informed written consent.…”
Section: Methodsmentioning
confidence: 99%
“…This study was registered in the Clinical Trial Registry (UMIN-CTR) as UMIN000035080. The detail was published as a protocol [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations